The Use of the Six English Tenses in Students’ Daily Conversation - Maulana Yusuf Aditya; Chairuddin Chairuddin (Universitas Dian Nuswantoro, 2020)
Abstract. For English learners, there are important aspects to consider such as vocabulary, pronunciation and grammar to master their speaking skills. Speaking is used to express people’s ideas and feelings in daily life or to communicate with others both personal talks and transactional conversation. The objective of the study is to figure out how the students of SMKN 2 Bangkalan can use the six English tenses in daily conversation. The research was done within two weeks starting from 22th April to 06th May 2019. Observation and interview were performed to collect the data. Observation was made to see what was going on in the class, focusing on the students’ conversation. On the other hand, Interview was carried out to know the students’ problems in using the correct tenses in conversation, and to find out how the students solve the problems. The observation shows that in using the six English tenses, the students likely found it hard to apply the correct tenses in the conversation with their friends and the teacher. The students tended to use one tense in all situations and the tense mostly used was the simple present one. From the interview, it is found that the students do not really understand what tenses are, either the meaning or the uses.Keywords: daily conversation, tenses, observation, interview, contexts of situationAbstrak. Bagi pembelajar Bahasa Ingggris, terdapat aspek penting seperti kosakata, pengucapan dan tatabahasa yang harus diperhatikan untuk meningkatkan kemampuan berbahasa Inggrisnya. Kemampuan berbicara khususnya digunakan untuk menyampaikann semua yang ada dalam benak kita seperti misalnya ide dan perasaan dalam kehidupan sehari-hari, baik itu berupa perkataan pribadi atau pun percakapan transaksional. Tujuan utama penelitian ini adalah untuk mengetahui bagaimana murid dapat menggunakan enam kala (tenses) dalam percakapan sehari-hari sesuai dengan kontek situasi, di SMKN 2 Bangkalan. Penelitian dilakukan selama 2 minggu dimulai tanggal 22 April s/d 06 Mei 2019. Penelitian dilakukan dengan 2 langkah seperti observasi dan wawancara. Observasi dilakukan untuk mengetahui yang terjadi dalam selama proses pembelajaran dan fokus pada cara murid bercakap. Wawancara dilakukan oleh peneliti untuk mengetahui permasalahan pada murid dalam menggunakan tenses yang benar dan bagaimana murid mengatasi masalah penggunaan kala yang benar tersebut. Dari hasil observasi dapat diketahui bahwa penggunaan enam kala dalam percakapan sehari-hari dari murid adalah buruk, mereka tidak bisa mengaplikasikan kala yang sesuai dalam percakapan, baik dengan teman dan guru. Mereka cenderung menggunakan satu kala dalam percakapan dalam konteks situasi yang berbeda dan tense yang digunakan adalah Simple Present Tense.Kata kunci: percakapan, kala, observasi, wawancara, konteks situasi